ANTI-MICROBIAL, ANTI-OXIDANT & PHYTOCHEMICAL ANALYSIS oF Citrus aurantium (ORANGE) LEAF EXTRACT - Rao, Nirmala Babu; Kumari, O. Sita; Gajula, Rajesh Goud (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
The present investigation was carried out to evaluate anti-microbial, anti-oxidant andphytochemical compound properties of citrus aurantium leaves. Plants have been the majororiginal source of many drugs used in the treatment of diseases today. Antimicrobial, Antioxidativesystems and the contents of phytochemical compounds were investigated in leavesof sour orange trees that are grown under atmospheric co2 concentrations. Phytochemicalcompounds which are extracted with methanol, ethanol, acetone and distilled water withdifferent medicinal properties. The plant extracts were subjected to preliminaryphytochemical screening for the presence of alkaloids, carbohydrates, glycosides, tannins,phenolic compounds, proteins, free amino acids, saponins, phytosterols, and flavonoids. Theanti-microbial activity was carried out with two gram positive bacteria i.e., Staphylococcusaureus, Bacillus subtilis and two gram negative bacteria i.e., Escherichia coli, Salmonellatyphi by agar well diffusion method. The anti-oxidant properties of these plant extracts ofvarious concentrations (50,150,250 µg/ml) was determined by using methods like DPPHradical scavenging, hydroxyl radical scavenging, superoxide anion, hydrogen peroxide andnitrous oxide the results are compared with known standards. The plant extracts will inhibitfree radicals at all concentrations tested. A systematic investigation is carried out to evaluatethe total phenolics and flavonoid to explore relation with anti-oxidant properties.